Pengaruh Red Flags, Skeptisme Profesional, Pengalaman Audit, dan Independensi Terhadap Kemampuan Auditor Dalam Mendeteksi Fraud - Muhammad Hirza Alby; Indah Rahayu Lestari (Nirta Learning Centre, 2025)
This study aims to determine the Effect of Red Flags, Professional Skepticism, Audit Experience, Independence on Auditor's Ability to Detect Fraud in Auditors at Public Accounting Firms in the Jakarta Region. The data sampling technique was through direct questionnaire distribution to respondents using the convenience sampling method. The population in this study were auditors working in 274 Public Accounting Firms by distributing questionnaires to 150 respondents, while 74 respondents responded as samples in this study. This study uses multiple linear regression analysis techniques and uses the Statistical Package For The Social Science (SPSS) version 22 and Microsoft Excel 2019 program test tools. The results of this study prove that the red flags variable has a positive and significant effect on the auditor's ability to detect fraud, while professional skepticism, audit experience and independence do not affect the auditor's ability to detect fraud.